(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2011)
The purpose of this study was to compare the anxiety reported by deaf and normal hearing teenagers on the Public Speaking Simulation Test through the Humor Analog Scale (HAS). Fifteen deaf teenagers expert on the digital alphabet and on the Brazilian Sign Language (Libras) and fifteen normal hearing (control group) with 11 to 18 years of age participated on the study. Social economic class and genre were similar in the two groups. Both groups were individually submitted to a Public Speaking Simulation Test, and evaluated by the Humor Analog Scale applied on the adaptation phase, pre-speech phase, during the speech phase and after the speech phase. For the teenager population the test did not cause anxiety, typically obtained with adults. There was no significant statistic difference between the two different language groups.